2018
DOI: 10.3390/ijms19113388
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of All-Trans Retinoic Acid on Gastric Cancer: A Narrative Literature Review

Abstract: Gastric cancer (GC) is the third leading cause of cancer-related death worldwide with a five-year survival rate of around 25%, and 4% when diagnosed at a metastatic stage. Cancer stem cells (CSC) have recently been characterized as being responsible for resistance to radio/chemotherapies and metastasis formation, opening up perspectives for new targeted therapies. Those CSCs express biomarkers such as cluster of differentiation 44 (CD44) and display high aldehyde dehydrogenase activity that converts vitamin A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 126 publications
2
25
0
Order By: Relevance
“…Recently, the literature has been pointing out a relationship between nutrients with antioxidant function and cancer therapy. Among the antioxidants studied, some have been highlighted, such as vitamin A due to its role in cancer therapy, given its chemoprotective and antioxidant role, which is able to decrease, in the short and long term, the harmful effects of cancer treatment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the literature has been pointing out a relationship between nutrients with antioxidant function and cancer therapy. Among the antioxidants studied, some have been highlighted, such as vitamin A due to its role in cancer therapy, given its chemoprotective and antioxidant role, which is able to decrease, in the short and long term, the harmful effects of cancer treatment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…GC is the third most common cause of cancer-related mortality worldwide, and has attracted much attention due to its relatively high rates of incidence and mortality (3). Although surgical resection and chemotherapy are the mainstream methods of treating this malignancy, patients suffering from advanced stage GC have poor prognoses and high mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, gastric cancer (GC) is the fifth most common malignant tumor and the third leading cause of cancer-related mortality (1). The 5-year survival rate of GC remains low (25%) (2,3). Although great progress has been made in the availability of treatment techniques for GC, the prognosis for GC patients remains poor due to the biological properties of tumor cells, including a high propensity for invasiveness and metastasis, rapid proliferation, and anti-apoptotic behavior (4).…”
Section: Introductionmentioning
confidence: 99%
“…was first reported in 1926, when it was observed that that gastric cancers were increased in rats fed a vitamin A-deficient diet [12][13]. Later experimental data demonstrated that all-trans retinoic acid (ATRA) was effective against leukemia and induced the differentiation of HL-60 leukemia cells, as well as inhibited the growth of gastric and breast cancers [14][15]. ATRA is the preferred isomer as compared with the cis-retinoic acid isomer, and it has been demonstrated that ATRA has better efficiency both in vitro and in vivo [14][15].…”
mentioning
confidence: 99%
“…Later experimental data demonstrated that all-trans retinoic acid (ATRA) was effective against leukemia and induced the differentiation of HL-60 leukemia cells, as well as inhibited the growth of gastric and breast cancers [14][15]. ATRA is the preferred isomer as compared with the cis-retinoic acid isomer, and it has been demonstrated that ATRA has better efficiency both in vitro and in vivo [14][15]. Thus, along with vitamin D, vitamin A (retinol, retinoic acid) and the carotenoids have also been shown to have a significant impact on cancer chemoprevention and treatment, most notably in cancers derived from epithelial tissues [12][13][14][15][16].…”
mentioning
confidence: 99%